Aortic valve replacement in patients aged 50 to 69 years: Analysis using Korean National Big Data. Issue 11 (2nd September 2022) - Kim, Min‐Seok; Kim, Hae Rim; Lee, Seung Hyun; Lee, Sak; Joo, Hyun‐Chel
Abstract: Background: The aim of this study was to compare the clinical outcomes and long‐term survival in patients who underwent isolated aortic valve replacement (AVR) with mechanical versus bioprosthetic valves. Methods: Patients aged 50–69 years who had undergone AVR from 2002 to 2018 were identified and their characteristics were collected from Korean National Health Information Database formed by the National Health Insurance Service, Republic of Korea. Of the 5792 patients, 1060 patients were excluded due to missing values on characteristics. Of the 4732 study patients, 1945 patients (41.1%) had received bioprosthetic valves (Group B) and 2787 patients (58.9%) had received mechanical valves (Group M). A propensity score‐matched analysis was performed to match 1429 patients in each group. Data on mortality, cardiac mortality, reoperations, cerebrovascular accidents, and bleeding complications were obtained. Results: The overall survival rates at 5 and 10 years postoperatively were 87.8% and 75.2% in the matched Group B and 91.2% and 76.7% in the matched Group M, respectively ( p = .140). Freedom from cardiac death rates at postoperative 5 and 10 years were 95.6% and 92.4% in the matched Group B and 96.0% and 92.1% in the matched Group M, respectively ( p = .540). The cumulative incidence of reoperation was higher in the matched Group B than in the matched Group M ( p = .007), and the cumulative incidence of major bleeding was higher in the matched Group M than in the matched Group B ( p = .039). Conclusion: In patients aged 50–69 years who underwent isolated AVR, the patients who received bioprosthetic valves showed similar cardiac mortality‐free survival and long‐term survival rates to the patients who received mechanical valves.